Redescription of the larva of Amblyomma oblongoguttatum Koch, 1844 (Acari: Ixodidae) by light and scanning electron microscopy - Barbieri, Fabio S.; Brito, Luciana G.; Barros-Battesti, Darci M.; Famadas, Kátia M.; Labruna, Marcelo B.; Camargo, Luis Marcelo A. (Zootaxa, 2012)
The larval stage of Amblyomma oblongoguttatum Koch is redescribed using optical and scanning electron microscopy.Unfed larvae were obtained from a colony of A. oblongoguttatum originated from engorged females collected on domesticpigs from Monte Negro municipally (10°29’S, 63°32’W), State of Rondônia, Western Amazon, Brazil. Several charactersare presented including the chaetotaxy of the idiosoma, palpi and Haller’s organ, as well as morphological features of theidiosoma, gnathosoma and legs. In addition, the porotaxy (topographical and numerical patterns of integumentary struc-tures) were presented by using a new nomenclature recently proposed. The chaetotaxy of the larvae of A. oblongoguttat-um, in general, is similar to other Neotropical Amblyomma species. Three types of integumentary structures were observedon the idiosoma: lyrifissures, small glands, and large wax glands. Topographic and numerical patterns of the integumen-tary structures consisted of 5 pairs of large wax glands (1 dorsal/ 4 ventral), 24 pairs of lyrifissures (11 dorsal/ 13 ventral),and 49 pairs of small glands (28 dorsal/ 21 ventral). These topographic and numerical patterns found for A. oblongogut-tatum show only minor differences when compared with patterns of other Amblyomma larvae, however, a few key features can be used for identification of these species.